2020
DOI: 10.1021/acs.chemrestox.0c00050
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicology of Nanomaterials

Abstract: The remarkable advances coming about through nanotechnology promise to revolutionize many aspects of modern life; however, these advances come with a responsibility for due diligence to ensure that they are not accompanied by adverse consequences for human health or the environment. Many novel nanomaterials (having at least one dimension <100 nm) could be highly mobile if released into the environment and are also very reactive, which has raised concerns for potential adverse impacts including, among others, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 199 publications
(417 reference statements)
0
51
0
Order By: Relevance
“…Earlier studies identified the (central) nervous system as an important target for the toxic effects of metal and metal-oxide nanoparticles [39][40][41]. Metal and metal-oxide nanoparticles can enter the brain by crossing the blood-brain-barrier (BBB) or can surpass this barrier via retrograde transport through olfactory nerve endings [38,[42][43][44].…”
Section: Main Text Neurotoxicity Of Chemically Inert Metal(oxide) Nanoparticlesmentioning
confidence: 99%
“…Earlier studies identified the (central) nervous system as an important target for the toxic effects of metal and metal-oxide nanoparticles [39][40][41]. Metal and metal-oxide nanoparticles can enter the brain by crossing the blood-brain-barrier (BBB) or can surpass this barrier via retrograde transport through olfactory nerve endings [38,[42][43][44].…”
Section: Main Text Neurotoxicity Of Chemically Inert Metal(oxide) Nanoparticlesmentioning
confidence: 99%
“…[46][47] Compared with larger particles, ultrafine particles are far more numerous, highly reactive, and able to gain access to all major organs of the body. [48][49][50][51] Of particular concern, transition metal-rich NPs, such as those formed abundantly as combustion-and friction-derived nanoparticles (CFDNPs), may act as catalysts for formation of reactive oxygen species (ROS) and for protein misfolding, aggregation and fibril formation. 7, 10, 12,14-18, 32,33, 41, 53-63 Here, we investigate AD and PD neuropathological hallmarks in the brainstem in young MMC residents, and their associations with the presence, location and composition of exogenous, metal-rich NPs in the brainstem and cerebellum.…”
mentioning
confidence: 99%
“…It is reported that most of the innovative nanomaterials are highly mobile, easily dispersible, and very reactive once they are released into the environment, i.e., soil, air, and water, posing a potential threat to human health [ 162 ]. Regarding the release, it has been observed some metals, e.g., silver (Ag) and Cu, and metal oxides, e.g., ZnO and iron oxide (FeO), may dissolve quickly, while others, e.g., TiO 2 , silicon dioxide (SiO 2 ), CNTs, graphene, are more persistent and may pose potential risks and hazards [ 163 ]. The prevailing exposure routes of humans to nanomaterials are inhalation (major exposure route), ingestion, and dermal routes, the last being considered negligible.…”
Section: Environmental and Health Risks Assessmentsmentioning
confidence: 99%